Inter-relation between Indonesian Islamic Capital Market Index and the World Market Indices: Period of January 2009 – December 2017 - Bhakti, Dwi Pramaya; Widjaja, Hidajat Sofyan (The Indonesian Capital Market Review, 2020)
The purpose of this study is to investigate the relationship between the Jakarta Islamic Index andthe Shariah World Indices within period of January 2009 to December 2017. This study is conducted using vector autoregressive (VAR) method and tawhidi string relationship (TSR) method. The key finding is the conventional Sharia Migration to Sharia in Indonesia through several channel and must be followed by developing the stock market platform as well as Screening on stock shares that follow the principles of sharia. This study found that Middle East investors reflected in the active GCC index in investing in the Indonesian capital market. Under such a phenomenon, the Capital Market Regulators in Indonesia, in this case OJK, must be active in enhancing the Indonesian market among the Gulf countries as well as the OIC (Organizing Islamic Countries). The managerial implications of this study encourage issuers belonging to the Islamic index to continue to improve healthier financial performance while making a breakthrough with the Islamic index in the world, especially the GCC countries.